Effect of exercise modality and intensity on postexercise Interleukin-6 and Hepcidin levels - Sim, M.; Dawson, B.; Landers, G.; Swinkels, D. W.; Tjalsma, H.; Trinder, D.; Peeling, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
The effect of exercise modality and intensity on Interleukin-6 (IL-6), iron status, and hepcidin levels was investigated. Ten trained male triathletes performed 4 exercise trials including low-intensity continuous running (L-R), low-intensity continuous cycling (L-C), high-intensity interval running (H-R), and high-intensity interval cycling (H-C). Both L-R and L-C consisted of 40 min continuous exercise performed at 65% of peak running velocity (vVO2peak) and cycling power output (pVO2peak), while H-R and H-C consisted of 8 × 3-min intervals performed at 85% vVO2peak and pVO2peak. Venous blood samples were drawn pre-, post-, and 3 hr postexercise. Significant increases in postexercise IL-6 were seen within each trial (p < .05) and were significantly greater in H-R than L-R (p < .05). Hepcidin levels were significantly elevated at 3 hr postexercise within each trial (p < .05). Serum iron levels were significantly elevated (p < .05) immediately postexercise in all trials except L-C. These results suggest that, regardless of exercise mode or intensity, postexercise increases in IL-6 may be expected, likely influencing a subsequent elevation in hepcidin. Regardless, the lack of change in postexercise serum iron levels in L-C may indicate that reduced hemolysis occurs during weight-supported, low-intensity activity.